Extra yarn - Barnett, Mac.; Klassen, J. (New York, N.Y. : Balzer & Bray, 2012)
With a supply of yarn that never runs out, Annabelle knits for everyone and everything in town until an evil archduke decides he wants the yarn for himself.
Keywords: Yarn -- Fiction; Knitting -- Fiction; Humorous stories